Violence against parents: key factors analysis. - Aroca-Montolío, Concepción; Lorenzo-Moledo, Mar; Miró-Pérez, Camilo (Anales de Psicología / Annals of Psychology, 2013)
The Prosecutor’s Office of Spain, in the 2009 October report, emphasized that the violence of sons and daughters against parents was the most disturbing crime among those committed by underage adolescents because of an increase in prevalence and incidence. For this reason, it is important to understand some characteristics of the families who suffer it and the children who ill-treat. To achieve these objectives, we have carried out a  bibliometric review of  qualitative analyses, on the basis of documents and books from 1957 until 2011, mainly from countries such as Australia, Japan, Canada, New Zealand, France, USA or Spain, from which we  intend to understand: (a) what  the violence against parents is, (b) the cycle of this kind of violence, (c) characteristics of the families who suffer this violence, and (d) the characteristics of  the children who ill-treat. In the same way, with the information that emerges from this review of research, we can know the state of the question in order to define guidelines focused on the design of new research of violence of children under age.